Experiences of HIV-positive postpartum women and health workers involved with community-based antiretroviral therapy adherence clubs in Cape Town, South Africa - Trafford, Zara (BMC Public Health, 2018)
BACKGROUND: The rollout of universal, lifelong treatment for all HIV-positive pregnant and breastfeeding women (“Option B+”) has rapidly increased the number of women initiating antiretroviral treatment (ART) and requiring ART care postpartum. In a pilot project in South Africa, eligible postpartum women were offered the choice of referral to the standard of care, a local primary health care clinic, or a community-based model of differentiated ART services, the adherence club (AC). ACs have typically enrolled only non-pregnant and non-postpartum adults; postpartum women had not previously been referred directly from antenatal care. There is little evidence regarding postpartum women’s preferences for and experiences of differentiated models of care, or the capacity of this particular model to cater to their specific needs. This qualitative paper reports on feedback from both postpartum women and health workers who care for them on their respective experiences of the AC. METHODS: One-on-one in-depth qualitative interviews were conducted with 19 (23%) of the 84 postpartum women who selected the AC and were retained at approximately 12 months postpartum, and 9 health workers who staff the AC. Data were transcribed and thematically analysed using NVivo 11. RESULTS: Postpartum women’s inclusion in the AC was acceptable for both participants and health workers. Health workers were welcoming of postpartum women but expressed concerns about prospects for longer term adherence and retention, and raised logistical issues they felt might compromise trust with AC members in general. CONCLUSIONS: Enrolling postpartum women in mixed groups with the general adult population is feasible and acceptable. Preliminary recommendations are offered and may assist in supporting the specific needs of postpartum women transitioning from antenatal ART care. TRIAL REGISTRATION: Number NCT02417675 clinicaltrials.gov/ct2/show/record/NCT02417675 (retrospective reg.)